Dentin slice model of dental stem cells in a fibrin-agarose construct for dental pulp regeneration - Carolina Inostroza; Claudia Brizuela; Macarena Hernández; Javiera Ortiz; Ana María Vega-Letter; Flavio Carrión (Universidad de Concepción., 2022)
Objectives: To implement a dentin slice model of mesenchymal stem cells derived from dental tissues in a fibrin-agarose construct for dental pulp regeneration. Material and Methods: MSCs derived from different oral cavity tissues were combined with a fibrin-agarose construct at standard culture conditions. Cell viability and proliferation tests were assayed using a fluorescent cell dye Calcein/Am and WST-1 kit. The proliferation assay was evaluated at 24, 48, 72, and 96 hours. Also, we assessed the dental pulp stem cells (DPSCs) cell morphology inside the construct with histological stains such as Hematoxylin and Eosin, Masson's trichrome, and Periodic acid-Schiff. In addition, we elaborated a tooth dentin slice model using a culture of DPSC in the fibrin-agarose constructs co-adhered to dentin walls. Results: The fibrin-agarose construct was a biocompatible material for MSCs derived from dental tissues. It provided good conditions for MSCs' viability and proliferation. DPSCs proliferated better than the other MSCs, but the data did not show significant differences. The morphology of DPSCs inside the construct was like free cells. The dentin slice model was suitable for DPSCs in the fibrin-agarose construct. Conclusion: Our findings support the dentin slice model for future biological use of fibrin-agarose matrix in combination with DPSCs and their potential use in dental regeneration. The multipotency, high proliferation rates, and easy obtaining of the DPSCs make them an attractive source of MSCs for tissue regeneration.